Fibre Proportion in Oral Nutritional Supplements on Diarrhea Management in Cancer Patients: A Case Study - Neoh, May Kay; Jamhuri, Norshariza; Ng, Wai Han; Mohd Haniff Lai, Betti Sharina; Musa, Aini; Mohd Samwil, Siti Nuraini; Abdullah, Aeininhayatey; Zakaria, Nor Adlina; Ho, Chiou Yi (Asian Pacific Journal of Cancer Care, 2025)
Background and purpose: Diarrhea is a common side effect in cancer patients, especially during chemotherapy or antibiotic treatment. Managing this symptom is important for patient comfort, hydration, and nutritional status. Fibre, an important component of many oral nutritional supplements (ONS) formulations, has been shown to influence bowel function, including diarrhea. This case study examines the role of fibre proportion in ONS for managing diarrhea in two cancer patients undergoing treatment. Case presentation: Both patients initially experienced persistent diarrhea despite switching to fibre-based ONS. Upon transitioning to an ONS with an equal ratio of soluble to insoluble fibre, both patients showed improved stool consistency and bowel open frequencies with optimal energy and protein intake. Discussion: The proportion of soluble to insoluble fibre in ONS may play a crucial role in managing diarrhea among cancer patients. While achieving adequate total fibre intake is important, healthcare providers may need to consider not just the quantity but also the quality and proportion of fibre in nutritional interventions. Soluble fibre-enriched ONS may offer benefits for reducing diarrhea, while high insoluble fibre content could aggravate the condition. Conclusion: A careful consideration of the types and proportions of fibre may be necessary for optimal symptom management. A tailored approach that accounts for the patient’s specific needs is essential in optimizing nutritional care and improving quality of life.